Bacterial Biotransformation of Pentachlorophenol and Micropollutants Formed during Its Production Process - Lopez-Echartea, Eglantina; Macek, Tomas; Demnerova, Katerina; Uhlik, Ondrej (International journal of environmental research and public health, 2016)
Pentachlorophenol (PCP) is a toxic and persistent wood and cellulose preservative extensively used in the past decades. The production process of PCP generates polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) as micropollutants. PCDD/Fs are also known to be very persistent and dangerous for human health and ecosystem functioning. Several physico-chemical and biological technologies have been used to remove PCP and PCDD/Fs from the environment. Bacterial degradation appears to be a cost-effective way of removing these contaminants from soil while causing little impact on the environment. Several bacteria that cometabolize or use these pollutants as their sole source of carbon have been isolated and characterized. This review summarizes current knowledge on the metabolic pathways of bacterial degradation of PCP and PCDD/Fs. PCP can be successfully degraded aerobically or anaerobically by bacteria. Highly chlorinated PCDD/Fs are more likely to be reductively dechlorinated, while less chlorinated PCDD/Fs are more prone to aerobic degradation. The biochemical and genetic basis of these pollutants' degradation is also described. There are several documented studies of effective applications of bioremediation techniques for the removal of PCP and PCDD/Fs from soil and sediments. These findings suggest that biodegradation can occur and be applied to treat these contaminants.
Keywords: Bacteria; pentachlorfenol; biodegradace; Benzofurans; benzofurany; pentachlorophenol; Polychlorinated Dibenzodioxins; Humans; Pentachlorophenol; polychlorinated dibenzofurans; wood preservation; biotransformace; půda; polychlorinated dibenzo-p-dioxins; Soil; Biotransformation; contaminated soil; bacterial degradation; polychlorované dibenzodioxiny; Soil Pollutants; bioremediation; lidé; Biodegradation, Environmental; látky znečišťující půdu